2019
DOI: 10.1177/1060028019828420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of a Patient Decision Aid for Atrial Fibrillation Stroke Prevention Therapy

Abstract: Background: Stroke prevention therapy decisions for patients with atrial fibrillation (AF) are complex and require trade-offs, but few validated patient decision aids (PDAs) are available to facilitate shared decision making. Objective: To evaluate the effects of a novel PDA on decision-making parameters for AF patients choosing stroke prevention therapy. Methods: We developed an evidence-based individualized online AF PDA for stroke prevention therapy and evaluated it in a prospective observational pilot stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…Table 1 and Supplementary Material 5 describe the 14 included SDM tools. 31 55 All but 2 were in English; the mAF app 42 was in Chinese and MATCh AFib 43 , 44 in Portuguese. When examining their intended use, 3 were patient decision aids, 5 were encounter tools, 4 had features of both, and 2 were not classifiable because of either lack of information or access to the tool itself.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 and Supplementary Material 5 describe the 14 included SDM tools. 31 55 All but 2 were in English; the mAF app 42 was in Chinese and MATCh AFib 43 , 44 in Portuguese. When examining their intended use, 3 were patient decision aids, 5 were encounter tools, 4 had features of both, and 2 were not classifiable because of either lack of information or access to the tool itself.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies, including 2 randomized trials 42 , 48 and 4 nonrandomized studies, 34 , 43 , 53 , 55 at high risk of bias reported the effect of SDM tools on SDM outcomes ( Table 2 and Supplementary Material 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no evidence that directly addresses the role of shared decision-making in the context of ASA for primary prevention, although interventions to support shared decisionmaking have been evaluated for the treatment of hypertension, 25,26 atrial fibrillation 27 and diabetes. 28…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…On ne dispose actuellement d'aucune donnée probante quant au rôle de la prise de décision partagée dans le contexte d'un traitement avec l'AAS en prévention primaire, quoique des interventions visant à appuyer la prise de décision partagée ont été évaluées pour le traitement de l'hypertension artérielle 25,26 , de la fibrillation auriculaire 27 et du diabète 28 .…”
Section: Prise De Décision Partagéeunclassified